Inovasi Produk Ukm Putri Timus Melalui Timus Frozen - Sunardi Sunardi; Erni Suparti, Ida Giyanti, Sugiarti (Adi Widya : Jurnal Pengabdian Masyarakat, 2019)
The activities of the Program Pengembangan Produk Daerah (PPPUD) have been carried out at Micro small business (MSB) Putri Timus, which is held at Manggung RT 03 RW 08 Cangakan Karanganyar. This PPPUD activity is made in the framework of promoting the timus as a superior product in the Karanganyar area. MSB Putri Timus produce fried timus which is a typical Karanganyar food and souvenir. The fried timus that provides MSB has a specialty that is bligo (Benincasa hispida). But the drawback of this product is not durable, only last less than 24 hours. The purpose of this activity is to carry out production through frozen timus so that durability can be marketed outside the Karanganyar region. The method used to achieve the objectives is to increase knowledge about Good Production Methods (GMP) and freezer procurement. The result of this activity is the availability of freezers and the production of timus frozen by MSB Putri Timus. The resulting frozen timus specifications are available in a plastic bag containing 12 timus. This frozen thymus has a durability of more than 30 days.